1979
DOI: 10.1037/0096-3445.108.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic regularity, positional frequency, and visual processing of letter strings.

Abstract: Previous research has demonstrated that familiarity with the orthographic structure within a letter string can facilitate the processing of the component letters. The current research was directed at discovering the psychologically relevant properties of this structure. Two fundamental descriptions were independently varied in the construction of six-letter nonword strings. A probabilistic description based on the frequency of occurrence of letters in each position was factorially combined with a rule-governed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 29 publications
1
57
0
1
Order By: Relevance
“…Wasthere a variation in the orthographic structure of the high-and low-frequency words or of the words and nonwords in these studies? Studies by Mason (1975) and Massaro, Venezky, and Taylor (1979) suggest that the transitional probability (TP) of letter sequence is an important variable in word identification. The Chambers and Forster (1975) study indicated no correlation between the response times and the TPs of the bigrams or the trigrams of the letter sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Wasthere a variation in the orthographic structure of the high-and low-frequency words or of the words and nonwords in these studies? Studies by Mason (1975) and Massaro, Venezky, and Taylor (1979) suggest that the transitional probability (TP) of letter sequence is an important variable in word identification. The Chambers and Forster (1975) study indicated no correlation between the response times and the TPs of the bigrams or the trigrams of the letter sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The stimuli utilized in the matching-to-sample and priming phases were primarily from Massaro, Venezky, & Taylor (1979). The stimuli were permutations derived from the most frequent 150 six-letter English words in Kucera and Francis (1967) and which met the following criteria: (a) they were orthographically regular; (b) they were pronounceable; (c) they contained common vowel and consonant spellings; and (d) they had no more than three letters for a medial consonant cluster, if one occurred.…”
Section: Stimulimentioning
confidence: 99%
“…Because the stimuli were presented visually, it was necessary to control for variables likely to affect visual processing, and many researchers (see Carr, Posner, Pollatsek, &Snyder, 1979, andMassaro, Venezky, &Taylor, 1979) have argued that orthographic structure is one such variable. Although orthographic regularity was ensured by making all of the items legal English strings, additional control was imposed by equating conditions for average log bigram frequency (based on the counts of Mayzner & Tresselt, 1965).…”
Section: Stimulimentioning
confidence: 99%